2019
DOI: 10.1155/2019/1527328
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Profiles and Risk Factors of Preexisting Biliary Infection in Patients with Therapeutic Endoscopy

Abstract: Background. The bile infection may already exist before the administration of an interventional procedure, despite no clinical manifestations of cholangitis detected. Blood cultures remained negative even in more than half of the febrile cases with cholangitis. Risk factors associated with bacterial growth in bile before the intervention are not well defined. To establish the bacterial profiles isolated from the bile samples and to identify risk factors for bacterial colonization in the bile system. Methods. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
4
10
0
Order By: Relevance
“…The presence of microbiome in the biliary tree in non-pathological conditions is still controversial. Previous studies in the literature evaluated the bile composition in animals model or in patients with biliary tree diseases (in cholangitis, acute cholecystitis, and cholangiocarcinoma and presence of gallstone) using mostly ERCP to collect bile samples ( 3 , 20 , 21 ). The presence of a biliary induced pathological condition and the use of ERCP were the main limitations of these studies: indeed, Mahafzah et al demonstrated that ERCP was an independent factor associated with positive bile culture ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of microbiome in the biliary tree in non-pathological conditions is still controversial. Previous studies in the literature evaluated the bile composition in animals model or in patients with biliary tree diseases (in cholangitis, acute cholecystitis, and cholangiocarcinoma and presence of gallstone) using mostly ERCP to collect bile samples ( 3 , 20 , 21 ). The presence of a biliary induced pathological condition and the use of ERCP were the main limitations of these studies: indeed, Mahafzah et al demonstrated that ERCP was an independent factor associated with positive bile culture ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore a critical need to identify, at the bedside, which patients are at high risk for infection with multidrug-resistant pathogens, so that initial empiric therapy can be targeted at these patients without adversely affecting the rest of the patients with BTI. Unfortunately, many previous studies[ 6 7 12 13 ] have only identified a few risk factors that lead to multidrug-resistant bacterial infections in BTI patients, but no model has been constructed to predict the probability of multidrug-resistant bacterial infections in individual patients. We used a nomogram to build a simple, convenient and repeatable bedside prediction tool which predicts multidrug-resistant bacteria infection and differentiates low versus high risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…These five predictors are easy to obtain in clinical practice, even in developing countries, indicating that the model has a wide range of application. In the present study, the previous antibiotic use within 90 days and previous biliary surgery were not statistically significant in univariate analysis, but based on clinical experience and prior reports[ 5 6 7 12 13 ] we included these in the multivariate analysis. The results of multivariate analysis showed that previous antibiotic use within 90 days and previous biliary surgery were independent risk factors for multidrug-resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cholangitis may be observed as an adverse event after endoscopic retrograde cholangiopancreatography (ERCP) [2] and may delay diagnostic laparotomy or biliary surgery. Enterococci represent one of the three bacteria found most often in the bile fluid of patients with an obstructed bile duct [3]. Antimicrobial treatment of enterococci may be challenging because multidrug-resistant enterococci have been increasingly observed worldwide [4].…”
Section: Introductionmentioning
confidence: 99%